2010
DOI: 10.1038/onc.2010.531
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β regulates the sphere-initiating stem cell-like feature in breast cancer through miRNA-181 and ATM

Abstract: Recent studies indicate that a subset of cancer cells possessing stem cell properties, referred to as cancer-initiating or cancer stem cells (CSCs), play crucial roles in tumor initiation, metastasis and resistance to anticancer therapies. Transforming growth factor (TGF)-βs and their family members have been implicated in both normal (embryonic and somatic) stem cells and CSCs. In this study, we observed that exposure to TGF-β increased the population of breast cancer (BC) cells that can form mammospheres in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
214
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(225 citation statements)
references
References 32 publications
(49 reference statements)
9
214
0
2
Order By: Relevance
“…Luciferase reporter assays further confirmed the potential binding of miR-181a to the 3'UTR of BCL2 in chondrocytes. This is in agreement with previous studies wherein miR181a binding to the 3'UTR of BCL2 was demonstrated in hepatocytes [14].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Luciferase reporter assays further confirmed the potential binding of miR-181a to the 3'UTR of BCL2 in chondrocytes. This is in agreement with previous studies wherein miR181a binding to the 3'UTR of BCL2 was demonstrated in hepatocytes [14].…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, TGF-β primarily acts via activation of Smad, a signal transducer protein which translocates to the nucleus and binds to Smad responsive promoter regions, thereby resulting in transcriptional modulation of target miRNAs and mRNAs [25]. Importantly, TGF-β has also been shown to cause up regulation of miR-181a in hepatocytes [16] and breast cancer cells [14]. Furthermore, TGF-β levels are reported to be elevated in the synovial fluid of OA patients [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In colorectal cancer, miR-181a has been associated with poor prognosis (13). In addition, miR-181 family members have been implicated with acquisition of the CSC phenotype in hepatic cancer (14) and in breast cancer (15). As such, miR-181a serves as a marker for increased "stemness" and invasive ability.…”
Section: Introductionmentioning
confidence: 99%
“…Other evidence also showed miR-181 was elevated in breast cancer stem cells. Overexpression of miR-181a/b, or depletion of its target ataxia telangiectasia mutated(ATM), was sufficient to induce sphere formation in breast cancer cells and promote tumorgenesis 108 .…”
Section: Oncogenesmentioning
confidence: 99%